HARMONISASI PENGATURAN PERLINDUNGAN KEKAYAAN INTELEKTUAL OLEH PEMERINTAH DAERAH - Fauzani, Muhammad Addi (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is driven by the issue of widespread violations of intellectual property rights, which have occurred due to insufficient involvement of the Regional Government in intellectual property protection. Unfortunately, legislation concerning intellectual property remains incomplete, posing challenges for local governments in implementing effective protection measures. The objectives of this research are twofold: first, to analyze the role of the Regional Government in providing intellectual property protection; second, to formulate regional-level intellectual property regulations for greater coherence. This study employs a normative juridical approach with a statutory and conceptual framework. The research findings indicate the following: Firstly, despite having authority over intellectual property protection, the Regional Government faces challenges due to the partial nature of intellectual property laws and regulations—comprising at least six statutes. This complexity impedes the Regional Government's ability to comprehend, formulate, and enforce laws related to intellectual property. Therefore, harmonization is essential. Secondly, the harmonization of intellectual property regulations at the regional level involves the Regional Government conducting: a) an inventory of existing intellectual property laws and regulations; b) analysis, evaluation, and harmonization of their content, which will be incorporated into Regional Regulations on Intellectual Property Protection. These regulations must be grounded in a robust philosophical and sociological framework.